2019
DOI: 10.2351/1.5096126
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the effect of laser remelting for laser cladding nickel based alloy

Abstract: Laser cladding is a recently developed additive manufacturing technique, which is widely used in remanufacturing and sustainable manufacturing fields. However, the surface roughness of laser cladding layer often fails to meet the tribological functions and assembly requirements. In order to improve the surface finish quality of laser cladding, various techniques such as manual polishing, grinding, abrasive blasting, and chemical polishing were adopted. However, these methods have certain disadvantages, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Standard deviation analysis indicated, at both sliding distances evaluated, approximately 20% lower variation in the remelted to as-deposited condition. Similar results are reported by García et al (2016) and Zhao et al (2018). Although as-deposited samples showed a tendency of inversely proportional relation between microhardness and wear rate, this behavior was more pronounced in the remelted coating.…”
Section: Friction Coefficient Volumetric Loss and K Archard's Coefficientsupporting
confidence: 88%
See 4 more Smart Citations
“…Standard deviation analysis indicated, at both sliding distances evaluated, approximately 20% lower variation in the remelted to as-deposited condition. Similar results are reported by García et al (2016) and Zhao et al (2018). Although as-deposited samples showed a tendency of inversely proportional relation between microhardness and wear rate, this behavior was more pronounced in the remelted coating.…”
Section: Friction Coefficient Volumetric Loss and K Archard's Coefficientsupporting
confidence: 88%
“…Besides that, the fact that remelting posttreatment was applied immediately after the coatings deposition reduced the thermal gradient effect (tensile stresses resulting from the cooling process), contributing to this cracks elimination. In the results step (topic 3), authors will be indicated, such as Houdková et al (2014) and Zhao et al (2018), that report similar characteristics. Before and after tribological test, samples were cleaned in ethyl alcohol and dried.…”
Section: Microhardness Test and Pin-on-disk Tribological Test In Dry Mediummentioning
confidence: 99%
See 3 more Smart Citations